Evaluating surface and subsurface water storage variations at small time and space scales from relative gravity measurements in semiarid Niger. Issue 6 (10th June 2013) - Pfeffer, Julia; Champollion, Cédric; Favreau, Guillaume; Cappelaere, Bernard; Hinderer, Jacques; Boucher, Marie; Nazoumou, Yahaya; Oï, Monique; Mouyen, Maxime; Henri, Christopher; Le Moigne, Nicolas; Deroussi, Sébastien; et al.
Abstract : [1] The acquisition of reliable data sets representative of hydrological regimes and their variations is a critical concern for water resource assessment. For the subsurface, traditional approaches based on probe measurements, core analysis, and well data can be laborious, expensive, and highly intrusive, while only yielding sparse data sets. For this study, an innovative field survey, merging relative microgravimetry, magnetic resonance soundings, and hydrological measurements, was conducted to evaluate both surface and subsurface water storage variations in a semiarid Sahelian area. The instrumental setup was implemented in the lower part of a typical hillslope feeding to a temporary pond. Weekly measurements were carried out using relative spring gravimeters during 3 months of the rainy season in 2009 over a 350 × 500 m 2 network of 12 microgravity stations. Gravity variations of small to medium amplitude (≤220 nm s −2 ) were measured with accuracies better than 50 nm s −2, revealing significant variations of the water storage at small time (from 1 week up to 3 months) and space (from a couple of meters up to a few hundred meters) scales. Consistent spatial organization of the water storage variations were detected, suggesting high infiltration at the outlet of a small gully. The comparison with hydrological measurements and magnetic resonance soundings involved that most of the microgravity variations came from the heterogeneity in the vadose zone. The results highlight the potential of time lapse microgravity surveys for detecting intraseasonal water storage variations and providing rich space‐time data sets for process investigation or hydrological model calibration/evaluation. Key Points: Intensive gravity field surveying was conducted in a semi‐arid Sahelian area Gravity surveys revealed water storage variations at small time and space scales A large part of the gravity variability is attributed to the vadose zone